Cultivating Critical Thinking Among Journalism Students in the Digital Age - Echeandía, Rossana (2024)
The study aims to identify factors contributing to the development of critical thinking skills among opinion journalism students in a private university. A question-based teaching method was employed, utilizing a case study approach with a group of twelve students. Data collection involved interviews and surveys. The findings underscore the significance of fostering critical thinking and highlight the necessity for educators to be adequately prepared for effective implementation. Notably, the method not only stimulates students’ capacity for analysis and interpretation but also enhances their awareness of their capabilities, thus promoting active engagement and enriching the learning process in the digital age. In conclusion, the study emphasizes the imperative to cultivate critical thinking in journalism students and underscores the importance of equipping educators for digital platforms.